The composition of the mesenchymal stromal cell compartment in human bone marrow changes during development and aging - Maijenburg, Marijke W. (Ferrata Storti Foundation, 2012)
Life-long hematopoiesis depends on the support of mesenchymal stromal cells within the bone marrow. Therefore, changes in the hematopoietic compartment that occur during development and aging probably correlate with variation in the composition of the stromal cell microenvironment. Mesenchymal stromal cells are a heterogeneous cell population and various subtypes may have different functions. In accordance with others, we show that CD271 and CD146 define distinct colony-forming-unit-fibroblast containing mesenchymal stromal cell subpopulations. In addition, analysis of 86 bone marrow samples revealed that the distribution of CD271(bright)CD146(−) and CD271(bright)CD146(+) subsets correlates with donor age. The main subset in adults was CD271(bright)CD146(−), whereas the CD271(bright)CD146(+) population was dominant in pediatric and fetal bone marrow. A third subpopulation of CD271(−)CD146(+) cells contained colony-forming-unit-fibroblasts in fetal samples only. These changes in composition of the mesenchymal stromal cell compartment during development and aging suggest a dynamic system, in which these subpopulations may have different functions.